Saevus Corax captures the castle - Parker, K. J. (Parker, K. J. Corax trilogy, 2023)
"It's important to look after your crew when you're in the battlefield salvage business. It's stressful work at the best of times, and although your employees are unlikely to be happy it makes sense to keep them alive. So when Saevus Corax finds himself having to capture a castle to stop his men from being killed, he has no choice but to give it a try. Needless to say, the conventional rules of siegecraft are unlikely to be followed"--Back cover.